Structure of the Zagros fold and thrust belt in the Kurdistan Region, northern Iraq - De Vera, J.; Ginés, J.; Oehlers, M.; McClay, K.; Doski, J. (TRABAJOS DE GEOLOGÍA, 2009)
This study summarizes the regional structure of the Zagros fold and thrust belt in the Kurdistan Region of northern Iraq. The fold and thrust belt is dominated by a 10 to 12 km thick succession of Late Proterozoic to present-day strata that have been deformed into a series of NW-SE- to E-W-trending and SW- to NE-verging doubly-plunging folds and associated thrust faults. Regional structural styles, topography and the distribution of recent seismicity in the region suggest the structure of the fold belt is in part controlled by basement-involved structures.